1997
DOI: 10.1021/es9607547
|View full text |Cite
|
Sign up to set email alerts
|

OH Radical-Initiated Oxidation of 2-Butoxyethanol under Laboratory Conditions Related to the Troposphere:  Product Studies and Proposed Mechanism

Abstract: This type of study provides information on the reaction mechanism of the conversion of a substrate molecule, in this case a glycol ether, into its oxidation products under polluted tropospheric conditions. Such detailed pathways for the breakdown of the substrate molecule lead to the generation of photooxidants, mainly ozone, and are essential input data for computer modeling studies used to derive ozone-creating potentials of volatile organic compounds released into the atmosphere. The products formed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…From the mechanism proposed, PF is a product of hydrogen abstraction from methylene IV in the following structure: Using structure reactivity [12], a 39% propyl formate yield is expected. PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4].…”
Section: Discussionsupporting
confidence: 91%
“…From the mechanism proposed, PF is a product of hydrogen abstraction from methylene IV in the following structure: Using structure reactivity [12], a 39% propyl formate yield is expected. PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4].…”
Section: Discussionsupporting
confidence: 91%
“…[16] It is also possible that isomerization proceeds through five-or seven-membered transition states [Stemmler et al, 1997;Tuazon et al, 1998], as shown for the CH 2 = CHC(= CH 2 )CH 2 CH 2 CH(O . )C(OH)(CH 3 ) 2 radical formed from myrcene.…”
Section: Oh Radical Reactionsmentioning
confidence: 89%
“…It is also possible that isomerization proceeds through five‐ or seven‐membered transition states [ Stemmler et al , 1997; Tuazon et al , 1998], as shown for the CH 2 = CHC(= CH 2 )CH 2 CH 2 CH(O • )C(OH)(CH 3 ) 2 radical formed from myrcene. Subsequent reactions of the alkoxy radicals CH 2 = CHC(= CH 2 )CH(O • )CH 2 CH(OH)C(OH)(CH 3 ) 2 (formed from myrcene) and CH 2 = CHC(CH 2 O • ) = CHCH 2 CH(OH)C(OH)(CH 3 ) 2 and CH 2 = CHC(CH 3 ) = CHCH(O • )CH(OH)C(OH)(CH 3 ) 2 (formed from ocimene) could possibly lead to the formation of acetone, plus multifunctional coproducts that are not amenable to gas chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…For hydrocarbon molecules such as alkanes and alkenes,2 there is now a sufficient body of laboratory kinetic and thermodynamic data to enable the product distributions to be estimated via sets of empirical rules for the reactions of the hydrocarbon alkoxy radicals.3 In the case of oxygencontaining organic compounds, the data base for the reactions of the corresponding oxygen-containing alkoxy radicals is still too limited to develop the empirical approach.3 To provide more laboratory data on the atmospheric degradations of oxygen-containing compounds, detailed product and mechanistic studies of the atmospheric degradations of ethers4 and glycol ethers have been carried out. 5,6 In the present study we have extended this approach by investigating the mechanism of the atmospheric oxidation of a model ether, isobutyl isopropyl ether. This molecule contains two readily transferable tertiary CwH bonds together with a sufficiently large carbon skeleton to enable the resulting oxy radicals to undergo rapid isomerisation reactions.…”
mentioning
confidence: 99%